A THE IMPACT OF EMOTIONAL INTELLIGENCE, QUALITY OF WORK LIFE AND ORGANIZATIONAL CITIZENSHIP COMMITMENT ON EMPLOYEE PERFORMANCE PT. BINTANG INDONESIA LUMAJANG - Via Lailatur Rizki (Department of Management - Institut Shanti Bhuana, 2024)
This study aims to examine the influence of emotional intelligence, quality of work life, and organizational commitment on employees' performance. This study employed a census approach, encompassing the complete existing employee population of PT. Bintang Indonesia, which consisted of a sample size of 39 employees. The dependent variable used is employee performance, while the independent variable used is emotional intelligence, quality of work life, and organizational commitment. The data was gathered by the administration of a questionnaire, and the acquired data was analyzed using the multiple linear regression approach with the use of SPSS 26. The data analysis technique used a validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The present study's results indicate the effect of emotional intelligence on employee performance, Quality of Work Life affects on employee performance, and organizational commitment affects on employee performance. The concurrent effect of emotional intelligence, quality of work life, and organizational commitment on employee performance.